The roles of parents in supporting early childhood with ADHD and dyslexia to overcome learning difficulties - Yulsi Yulsi; Ivaniarahma Ivaniarahma; Putri Dewi Aprilia; Dhita Afifah; Adharina Dian Pertiwi; Wilda Isna Kartika (Universitas Ahmad Dahlan, 2025)
Parents play a crucial role for children learning success, especially for early childhood. Their role is particularly important for early childhood with special needs, including ADHD and dyslexia. Therefore, this study aims to explore the role of parents in supporting early childhood with ADHD and dyslexia to overcome their learning difficulties. The study used a qualitative approach, involving two children: an ADHD child and a dyslexia child, as well as their parents and therapists as the main participants. Data collection was conducted through semi-structured interviews and observation during therapy sessions at Rumah Terapi Liliput Samarinda and Anisa Therapy Center Samarinda. The results showed that the role of parents includes five important aspects: recognition support, psychological support, practical support, knowledge support, and community support. Children showed progress, such as increased vocabulary, reading and writing skills, focus improvement, and motor skills. However, challenges remain occur, particularly from insufficient inclusive school environment and the limited public understanding of ADHD and dyslexia. Thus, the pro-active parents and their understanding of their roles is an important key in support their children to overcome their learning barriers and promote optimal development.